2017
DOI: 10.1080/13880209.2016.1278455
|View full text |Cite
|
Sign up to set email alerts
|

Nitraria retusa fruit prevents penconazole-induced kidney injury in adult rats through modulation of oxidative stress and histopathological changes

Abstract: Context:Nitraria retusa (Forssk.) Asch. (Nitrariaceae) is a medicinal plant which produces edible fruits whose antioxidant activity has been demonstrated.Objective: The current study elucidates the potential protective effect of N. retusa fruit aqueous extract against nephrotoxicity induced by penconazole, a triazole fungicide, in the kidney of adult rats.Materials and methods: Adult Wistar rats were exposed either to penconazole (67 mg/kg body weight), or to N. retusa extract (300 mg/kg body weight) or to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 70 publications
7
36
0
Order By: Relevance
“…For our best of knowledge, there are no published data regarding the effect of Nitraria retusa extract on the anti-genotoxicity in in vivo mammalian cells. However, Chaâbane et al (2017) reported that N. retusa fruit extract exhibited a highly protective action against toxic effect of penconazole which induce kidney injury. They suggested that the protective action of N. retusa fruit extract could result from its content of the phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…For our best of knowledge, there are no published data regarding the effect of Nitraria retusa extract on the anti-genotoxicity in in vivo mammalian cells. However, Chaâbane et al (2017) reported that N. retusa fruit extract exhibited a highly protective action against toxic effect of penconazole which induce kidney injury. They suggested that the protective action of N. retusa fruit extract could result from its content of the phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to TEB caused a significant decrease in the body weight gain, which could be explained either by the decrease in food consumption and/or by the toxicity induced by this toxicant (42). However, we observed a significant increase in water consumption as shown in TEB-treated groups, which could be justified by the mechanism to counteract the toxicity induced by this fungicide (11). The additional effects of TEB treatment revealed an increase in the relative liver weight.…”
Section: Parameters and Treatmentsmentioning
confidence: 53%
“…They act as free radical scavengers preventing cells and tissue damage. Exogenous antioxidants obtained from natural sources are considered relatively safe and without undesirable side effects (11) Many medicinal plants have interesting biological and pharmacological activities and are used as therapeutic agents (12). Garlic (Allium sativum L.) belongs to the Alliaceae family (13).…”
Section: Introductionmentioning
confidence: 99%
“…SOD enzyme catalyzes the dismutation of superoxide anions into hydrogen peroxide (H2O2) that easily diffuses across cell membranes and cytosol. To attenuate this action, CAT and other enzymes are able to neutralize this reactive species, producing water (H2O) and molecular oxygen [55,56], while NPSH groups protect the cells against the cytotoxic effects of endogenous or exogenous electrophiles metabolites [57]. Thus, the increase of these antioxidants may have contributed to protect against lipid peroxidation in plasma.…”
Section: Discussionmentioning
confidence: 99%